how many children did george washington have

Answers

Answer 1

Answer:

Martha and George Washington had no children together, but they raised Martha's two surviving children. In 1773 her daughter Patsy died when she was 16 during an epileptic seizure. John Parke "Jacky" Custis left King's College that fall and married Eleanor Calvert in February 1774.

Step-by-step explanation:

Answer 2

Answer:

2

Step-by-step explanation:


Related Questions

If Samantha scored between 9.2 and 9.4 points how many points did she get

Answers

9.3 points. Look at the tenths place, whatever number is between 2 and 4 (3) is your answer.

Answer:

Yes. In between both of those would be 9.3. Best of luck to you! :)

-mark as brainliest please!- XD

What is cavalieris principle

Answers

Step-by-step explanation:

Cavalieri's Principle. A method, with formula given below, of finding the volume of any solid for which cross-sections by parallel planes have equal areas. This includes, but is not limited to, cylinders and prisms.

Find the distance between the points (6, -4) and (0, 5).

Answers

Answer:

3 square root 13

Step-by-step explanation:

I used the distance formula and I got this answer.

WHAT IS DISTANCE?

Distance is the length of the path linking two sites is the distance between them.

How to solve ?

Distance between two points is solved by formula

[tex]=\sqrt{(x1-x2)^2 +(y1-y2)^2}\\=\sqrt{(6-0)^2+(-4-5)^2} \\=\sqrt{36+81} \\=\sqrt{117} \\=10.81[/tex]

Hence distance between points is 10.81

Learn more about distance

https://brainly.com/question/17273444

#SPJ2

Learn more about distance

https://brainly.com/question/2854969

#SPJ2

evaluate 625-625÷25-25​

Answers

Hi !

625 - (625 ÷ 25) - 25 = 575

Answer:

575

Step-by-step explanation:

Following the order of operations, division is performed before subtraction

Given

625 - 625 ÷ 25 - 25 ← perform the division

= 625 - 25 - 25 ← now perform the subtraction

= 600 - 25

= 575

1200 mm long and 800 mm wide. What is the area in square meters

Answers

Answer: [tex]0.96\ m^2[/tex]

Step-by-step explanation:

We can make the conversion from milimeters to meters (Remember that [tex]1m=1,000\ mm[/tex]). Then:

[tex]1,200\ mm[/tex] to [tex]m[/tex]:

[tex](1,200\ mm)(\frac{1\ m}{1,000\ mm})=1.2\ m[/tex]

[tex]800\ mm[/tex] to [tex]m[/tex]:

[tex](800\ mm)(\frac{1\ m}{1,000\ mm})=0.8\ m[/tex]

Now, we need to use this formula for calculate the area of a rectangle:

[tex]A=lw[/tex]

Where "l" is the lenght and "w" is the width.

Knowing that:

[tex]l=1.2\ m\\w=0.8\ m[/tex]

We can substitute values into the formula. Then we get:

[tex]A=(1.2\ m)(0.8\ m)\\\\A=0.96\ m^2[/tex]

Final answer:

The area of the rectangular shape is 0.96 square meters.

Explanation:

To find the area of a rectangle, we multiply its length by its width. Given that the length is 1200 mm and the width is 800 mm, we can convert these measurements to meters by dividing each measurement by 1000. So, the length in meters is 1.2 m and the width in meters is 0.8 m. To find the area in square meters, we multiply the length and width in meters: Area = 1.2 m × 0.8 m = 0.96 m².

which of the following is the graph of the inequality y>-2x+3

Answers

The answer is " D. Graph D"

product of (6+i)(2+9i)

Answers

Answer:

(6 + i)(2 + 9i) = 3 + 56i

Step-by-step explanation:

Use FOIL: (a + b)(c + d) = ac + ad + bc + bd

and i² = -1

(6 + i)(2 + 9i) = (6)(2) + (6)(9i) + (i)(2) + (i)(9i)

= 12 + 54i + 2i + 9i²

= 12 + 54i + 2i + 9(-1)

= 12 + 54i + 2i - 9               combine like terms

= (12 - 9) + (54i + 2i)

= 3 + 56i

[tex](6+i)(2+9i)=18+54i+2i-9=9+56i[/tex]

Translate each phrase into an algebraic expression.
the quotient of thirty and three times a number

Answers

Answer:

30/3x

Step-by-step explanation:

Let

x ----> a number

we know that

The algebraic expression of the phrase" thirty" is equal to the number 30

The algebraic expression of the phrase"three times a number" is equal to multiply the number by 3 ----> 3x

therefore

"The quotient of thirty and three times a number" is equal to divide the number 30 by 3x

30/3x

Answer:  The correct option is (B) [tex]\dfrac{30}{3x}.[/tex]

Step-by-step explanation:  We are given to translate the following phrase into an algebraic expression :

"the quotient of thirty and three times a number."

Let the unknown number be represented by x.

Then, according to the given phrase, the algebraic expression can be written as :

[tex]E=\dfrac{30}{3\times x}\\\\\\\Rightarrow E=\dfrac{30}{3x}.[/tex]

Thus, the required algebraic expression is [tex]\dfrac{30}{3x}.[/tex]

Option (B) is CORRECT.

What is the common difference in this sequence: 4, 13, 22, 31, 40?

Answers

Answer:

9

Step-by-step explanation:

To find the common difference, take the second term and subtract the first term

13-4 =9

Lets check:

Take the third term and subtract the second term

22-13 =9

The common difference is 9

Answer:

9

Step-by-step explanation:

9 is the common difference between the numbers in this sequence

4 +9 = 13

13 +9 = 22

22 +9 = 31

31 +9 = 40

Therefore the common difference is 9

PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL ;)

"Angie read 3 books in 4 days, and each book contained 280 pages. if angie reads the same number of pages each day, how many pages did she read per day?"​

Answers

Answer:210

Step-by-step explanation:

3 x 280 = 840

840 ÷ 4 = 210

what is the domain of the function shown in the mapping?
a. x|x=-5, -3, 1, 2, 6
b. y|y=-9, -6, 0, 2, 4
c. x|x= -9, -6, -5, -3, 0, 1, 2, 4, 6
d. y|y= -9, -6, -5, -3, 0, 1, 2, 4, 6

Answers

Answer:

it's A

Step-by-step explanation:

The domain is all the input values which is x|x=-5,-3,1,2,6

Find the rule for (3,1) (6,2) (9,3) (12,4) (15,5)

Answers

Answer:

y = [tex]\frac{1}{3}[/tex] x

Step-by-step explanation:

Compare the values of y with the values of x for each ordered pair

x  y

3  1 → y = 3 ÷ 3

6  2 → y = 6 ÷ 3

9  3 → y = 9 ÷ 3 = 3

12 4 → y = 12 ÷ 3 = 4

15 5 → y = 15 ÷ 3 = 5

The y value in each case is the x value divided by 3

Hence rule is

y = [tex]\frac{1}{3}[/tex] x

EMERGENCY!!! SOMEONE HELP ASAP

Answers

Answer:

B

Step-by-step explanation:

Matrices are equal when they are of the same order and their corresponding entries are equal.

This is the case for the given matrix and matrix B

Answer:

The second option.

Step-by-step explanation:

It is the one that is marked.

The elements are the same and in the same location.

Last week Bill made a purchase of $56.78 before tax. This week, the same items on sale would have cost him $41.90 before tax. If the tax is 4%, how much could Bill have saved by buying the items on sale (including tax)?

Answers

I think $43.57 Bc 41.90 times .04 is 16.76 then move the decimal, and add 41.90+1.67=43.57

Simplify
3 to the negative power of 9
over 3 to the negative power of 12

Answers

Answer:

27

Step-by-step explanation:

3^-9/ 3^-12

Simply change the division into multiplication. The denominator will become numerator. We are doing so because the base are same.

3^-9 * 3^12

Negative sign of power 12 become positive

Add the powers because the base is same.

3^-9+12

3^3

3^3 means multiply 3 three times

3*3*3

=27....

Answer:

3^3 In scientific notation terms

Step-by-step explanation:

First let's look at this in a little more simple way

[tex]\frac{3^{-9}}{3^{-12}}[/tex]

there so know we can start,

First since the main number is 3, put that away to the side for now:

3<----------     [tex]\frac{-9}{-12}[/tex]

Then, we need to replace the / symbol or the fraction with a subtraction equation:

[tex]^{-9-(-12)}[/tex]

Next, we need to simplify:

[tex]^{-9 + 12}[/tex]

Then, simplify some more and you should get:

[tex]^{3}[/tex]

Finally, get back the original 3 and combine it with the smaller 3:

[tex]3^{3}[/tex]

THANK YOU! Please Thanks, Vote 5, Thanks on my profile, and Friend!

Pls Brainliest! It would mean a lot! ; )

Find the equation for the linear function that passes through the points ( see photo)

Answers

Answer:

f(x) = (-4/5)*x + 4

Step-by-step explanation:

The line which passes through these points will decrease y by 12 for every x increase of 15. This is the same as decreasing y by 4 for every x increase of 5. This means the slope (rise over run) is -4/5. If this is applied to the first point to find what y is at 0, then the point (0, 4) is on the line.

This means that f(x) = (-4/5)*x + 4

Answer:

[tex]\large\boxed{y=-\dfrac{4}{5}x+4}[/tex]

Step-by-step explanation:

The slope-intercept form of an equation of a line:

[tex]y=mx+b[/tex]

m - slope

b - y-intercept

The formula of a slope:

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

We have the points (-5, 8) and (10, -4). Substitute:

[tex]m=\dfrac{-4-8}{10-(-5)}=\dfrac{-12}{15}=-\dfrac{12:3}{15:3}=-\dfrac{4}{5}[/tex]

Put it to the equation of a line:

[tex]y=-\dfrac{4}{5}x+b[/tex]

Put the coordinates of the point (-5, 8) to the equation, and solveit for b:

[tex]8=-\dfrac{4}{5\!\!\!\!\diagup_1}(-5\!\!\!\!\diagup^1)+b[/tex]

[tex]8=4+b[/tex]           subtract 4 from both sides

[tex]4=b\to b=4[/tex]

Finally we have:

[tex]y=-\dfrac{4}{5}x+4[/tex]

Simplify each expression. e^(ln 1) = e^(ln 5x) =

Answers

[tex]\bf \textit{Logarithm Cancellation Rules} \\\\ log_a a^x = x\qquad \qquad \stackrel{\textit{we'll use this one}}{a^{log_a x}=x} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ e^{\ln(1)}=e^{\ln(5x)}\implies e^{\log_e(1)}=e^{\log_e(5x)}\implies 1=5x\implies \cfrac{1}{5}=x[/tex]

Answer: it’s 1 and 5x on edg

Step-by-step explanation:

what is a quadradic function

Answers

Answer: It is a polynomial function of degree 2 and whose graph is a parabola.

Step-by-step explanation:

By definition a quadratic function is a polynomial function of degree 2 and whose graph is a parabola.

The Standard form of a quadratic function is:

[tex]y= ax^2 + bx + c[/tex]

Where "a", "b" and "c" are real numbers ([tex]a\neq0[/tex])

The Vertex form of a quadratic function is:

[tex]y=a(x-h)^2+k[/tex]

Where the point (h,k) is the vertex of the parabola.

The Intercept form of a quadratic function is:

[tex]y=a(x-p)(x-q)[/tex]

Where "p" and "q" are the x-intercepts.

Final answer:

A quadratic function is a second-order polynomial of the form f(x) = ax² + bx + c, whose graph is a parabola. The solutions of quadratic equations are found by various methods to determine the roots or zeros of the function.

Explanation:

A quadratic function is a type of mathematical function that can be represented in the form f(x) = ax² + bx + c, where a, b, and c are constants, and a ≠ 0. This form is a second-order polynomial, as its highest exponent is 2. The graph of a quadratic function is a parabola, which can open upwards or downwards, depending on the sign of the a coefficient.

The solution of quadratic equations refers to finding the values of x that make the equation equal to zero. These solutions are also known as roots or zeros of the function.

To solve a quadratic equation, one can use different methods such as factoring, completing the square, using the quadratic formula, or graphing. Each of these methods provides a way to find the roots of the quadratic function.

PLEASE HELP EMERGENCY!!!!

Answers

Answer:

D

Step-by-step explanation:

Matrices are equal when they are of the same order and their corresponding entries are equal.

This is the case with the given matrix and matrix D

Help me if you can attachment linked
Thank You

Answers

Answer:

B) 4

Step-by-step explanation:

Tan is opposite/adjacent. That means that 3 is the opposite side while 4 is the adjacent side.

B) 4 is the correct answer

Need help. Thanks for helping me.

Answers

Answer:

F 4 ^ -2

Step-by-step explanation:

4 ^ -5

-----------------

4^-3

We know that a^b/ a^c = a^ (b-c)

4 ^ (-5 -  -3)

4 ^ (-5 +3)

4 ^ (-2)

F) 4^-2

I am dumb so it might be wrong

PLEASE HELP ASAP!

For what value of x will the output to the exponential equation, y=3.80e^-0.20x, be equal to 2?

a.3

c.2

b.4

d.1

Answers

Answer:

2

Step-by-step explanation:

1) Take the natural log of both sides, obtaining:

   -0.20x + ln 3.80 = ln 2

2)  Group the ln terms on the right side:  -0.20x = ln 2 - ln 3.80

3)  Find the natural logs of 2 and 3.80 and combine them:  -0.408, so that we have 0.20x = 0.408.

4) Solving for x, we get 2.03, or approx 2 (Answer C)

Answer:

a. 3 is the closest choice.

Step-by-step explanation:

2 = 3.80 e^-0.20x

e^-0.20x = 2/3.8

Taking logs:

-0.20x = ln(2/3.8) = -0.64185

x =  3.2.

An interval has the notation (2,14). Find the
distance from the midpoint of the interval to
either endpoint.

Answers

Answer:

The distance from the midpoint of the interval to  either endpoint is 6 units

Step-by-step explanation:

step 1

Find the midpoint of the interval

The formula to calculate the midpoint between two numbers is equal to

[tex]M=(\frac{x1+x2}{2})[/tex]

substitute

[tex]M=(\frac{2+14}{2})[/tex]

[tex]M=8[/tex]

step 2

Find the distance from the midpoint of the interval to  either endpoint.

14-8=6 units

or

8-2=6 units

therefore

The distance from the midpoint of the interval to  either endpoint is 6 units

To find the distance from the midpoint of the interval (2,14) to either endpoint, first find the midpoint, which is 8, then calculate the distance to either endpoint by subtracting the lower endpoint from the midpoint, resulting in a distance of 6 units.

The question asks to find the distance from the midpoint of the interval (2,14) to either endpoint. To start, we find the midpoint of the interval by adding the two endpoints together and dividing by 2:

Midpoint = \((2 + 14) / 2\) = \(16 / 2\) = 8

Next, we calculate the distance from the midpoint to one of the endpoints. The distance can be found by subtracting the lower endpoint from the midpoint:

Distance = \(8 - 2\) = 6

Therefore, the distance from the midpoint of the interval to either endpoint is 6 units.

1. Donna bought a coat on sale for $60.
That was 25% off ( less than the regular price).
What was the regular price?​

Answers

Answer:

$240

Step-by-step explanation:

If x is the missing number and 25% equals to 1/4 then 1/4 times x equals 60.

Then once you multiply x on both sides you get $240.

An estate of $656,000is left to three siblings. The eldest receives 6 times as much as the youngest. The middle sibling receives $15,000 more than the youngest. How much did each receive?

Answers

Step-by-step explanation:

If x is the amount the eldest receives, y is the amount the middle receives, and z is the amount the youngest receives, then:

x + y + z = 656000

x = 6z

y = z + 15000

Substituting the last two equations into the first:

(6z) + (z + 15000) + z = 656000

8z + 15000 = 656000

8z = 641000

z = 80125

Solving for the remaining variables:

x = 6z = 480750

y = z + 15000 = 95125

The eldest receives $480,750, the middle receives $95,125 and the youngest receives $80,125.

The youngest sibling receives $80,125, the middle sibling gets $95,125, and the eldest receives $480,750 from the $656,000 estate. The distribution complies with the stipulation that the eldest receives 6 times what the youngest does, and the middle sibling receives $15,000 more than the youngest.

The distribution of an estate of $656,000 among three siblings with specific conditions. Let's designate the amount the youngest sibling receives as y. According to the provided information, the eldest sibling receives 6 times as much as the youngest, meaning they receive 6y. The middle sibling receives y + $15,000. To find out how much each sibling receives, we need to solve the equation: y + 6y + (y + $15,000) = $656,000.

Add up the terms containing y: 8y + $15,000 = $656,000. Subtract $15,000 from both sides: 8y = $641,000. Divide both sides by 8 to find y:
y = $80,125.

Now, calculate each sibling's share:

The youngest receives y, which is $80,125.

The middle sibling receives y + $15,000, which is $95,125.

The eldest receives 6y, which is $480,750.

These calculations ensure that the total is $656,000, distributed according to the stipulated conditions.

What is the common difference of the sequence?
-4,-2, 0, 2, 4,.

d = - 2

d= 2

d = 2

d = 4

d = -4​

Answers

Answer:

d= 2

Step-by-step explanation:

To find the common difference, take the second term and subtract the first

-2 - (-4)

-2+4 = 2

We add 2 each time

Lets check

Take the third term and subtract the second

0- -2

0+2 =2

The common difference is 2

what is the simplified form of 4x+2/x+5 plus 3x-1/x+5

Answers

[tex]\bf \underset{\textit{same denominator}}{\cfrac{4x+2}{x+5}+\cfrac{3x-1}{x+5}}\implies \cfrac{(4x+2)+(3x-1)}{x+5}\implies \cfrac{7x+1}{x+5}[/tex]

Answer:

(7x+1)/(x+5)

Step-by-step explanation:

4x+2       3x-1

--------  +  ----------

x+5           x+5

Since the denominator is the same, we can add the numerators

4x+2   +    3x-1

-----------------------

x+5    

Combine like terms

7x+1  

-----------------------

x+5      

simplify the following fraction 2/5+4/6-1/3

Answers

Answer:

11/15

Step-by-step explanation:

First, get a common denominator of 30. 2/5 becomes 12/30. 4/6 becomes 20/30. 1/3 becomes 10/30.

Now we can add and subtract accordingly.

12/30 + 20/30 = 32/30.

32/30 - 10/30 = 22/30.

Finally, simplify the fraction.

22/30 becomes 11/15 when each number is divided by 2.

Answer: [tex]\frac{11}{15}[/tex]

Step-by-step explanation:

The first step is to find the Least Common Denominator of  the fractions. Descompose each denominator into its prime factors and muliply the commons and non-commons with the least exponent. Then:

[tex]5=5\\6=2*3\\3=3\\\\LCD=2*5*3=30[/tex]

Divide each denominator by the LCD and multiply this quotient by the corresponding numerator, add the products and then reduce the fraction.

Therefore you get:

[tex]=\frac{(2*6)+(4*5)-(1*10)}{30}=\frac{12+20-10}{30}=\frac{22}{30}=\frac{11}{15}[/tex]

12x^ay^b / ( - 6x^ay )

Answers

Answer:

[tex]-2y^{b-1}[/tex]

Step-by-step explanation:

[tex]\frac{12x^ay^b}{-6x^ay}[/tex]

In multiplication of fractions you can do this:

[tex]\frac{a}{c} \cdot \frac{b}{d}=\frac{a \cdot b}{c \dot d} \text{ or the other way around } \frac{a \cdot b}{c \dot d}=\frac{a}{c} \cdot \frac{b}{d}[/tex].

So that is exactly what we are going to do here:

[tex]\frac{12x^ay^b}{-6x^ay}[/tex]

[tex]\frac{12}{-6} \cdot \frac{x^a}{x^a} \cdot \frac{y^b}{y}[/tex]

We know that 12 divided by -6=12/-6 =-2.

We also know assuming x isn't 0 that x^a/x^a=1.

On the last fraction, the only thing you can do there to simplify is use the following law of exponents: [tex]\frac{v^m}{v^n}=v^{m-n}[/tex].

So we have

[tex]\frac{12x^ay^b}{-6x^ay}[/tex]

[tex]\frac{12}{-6} \cdot \frac{x^a}{x^a} \cdot \frac{y^b}{y}[/tex]

[tex](-2) \cdot (1) \cdot (y^{b-1})[/tex]

Simplifying a bit and leaving out the ( ).

[tex]-2y^{b-1}[/tex]

pLz help

Graph the linear equation. Find three points that solve the equation, then plot then on the graph.
x -3y= -6​

Answers

Answer:

So you will want to graph the following 3 points:

(0,2)

(3,3)

(-3,1)

Then connect the points.

Step-by-step explanation:

So we have the equation x-3y=-6.

I'm going to solve for y once so I don't have to do it 3 times when choosing a value for x.

x-3y=-6

Subtract x on both sides:

 -3y=-x-6

Divide both sides by -3:

   [tex]y=\frac{-x}{-3}+\frac{-6}{-3}[/tex]

Simplify where you can:

  [tex]y=\frac{1}{3}x+2[/tex]

So since this in the slope-intercept form, y=mx+b where slope is m and b is y-intercept we have that (0,2) is on our line.  If you plug in 0, you will get 2 like this y=1/3 (0)+2=0+2=2.  

Now I'm going to choose easy values to plug in, ones that are divisible by 3 since x is being multiplied by 1/3.

So if x=3, then [tex]y=\frac{1}{3}(3)+2=1+2=3[/tex], so (3,3) is on the line.

So if x=-3, then [tex]y=\frac{1}{3}(-3)+2=-1+2=1[/tex]. so (-3,1) is on the line.

So you will want to graph the following 3 points:

(0,2)

(3,3)

(-3,1)

Other Questions
Escoge la mejor respuesta.Este vestido me queda muy grande. Tiene otra talla?Se lo doy a muy buen precio.Es demasiado dinero.No. Es el ltimo que queda. Which of the following would increase the rate of a chemical reaction between hydrochloric acid (HCl) and solid zinc metal (Zn)? A. Decreasing the concentration of HCl B. Pulverizing the zinc metal into a fine powder C. Performing the reaction at a lower temperature D. Decreasing the amount of Zn An artificial satellite is in a circular orbit around a planet of radius r= 2.05 x103 km at a distance d 310.0 km from the planet's surface. The period of revolution of the satellite around the planet is T 1.15 hours. What is the average density of the planet? An example of institutional racism is when banks:A. Increase the lowest interest rates they charge on home mortgages.B. Refuse to give mortgage loan to someone who does not have a job.C. Use race as the basis for determining mortgage interest rates.D. Foreclose on homes owned by racial minority members who cannot pay their mortgage. 8) Use Reduction of order to solve. One solution of homogeneo x2y" +7xy' +5y =x 1 x>0 y1 = X here y1 is a solution of the corresponding homogeneous. Describe the four processes of magma differentiation.How does the rate of cooling impact crystal size? A solid uniform cylinder of mass 4.1 kg and radius 0.057 m rolls without slipping at a speed of 0.79 m/s. What is the cylinders total kinetic energy? How was the Homestead Act of 1862 partially responsible for the Dust Bowl? A Carnot heat engine has an efficiency of 0.200. If it operates between a deep lake with a constant temperature of 293.0 K and a hot reservoir, what is the temperature of the hot reservoir? O 352 K O 1760 K O 366 K 1470 K The brain region that exerts the most direct effects on the endocrine system is the __________. How many seconds are in 240 minutes? 10. Sketch the graph of -5x^2- 16xy +7y^2-198 0. Show the steps used in rotating the axes What is Euler's equation? 7. A sample of hydrogen gas is mixed with water vapor. The mix has a total pressure of 725 torr and the water vapor has a partial pressure of 24 torr. What amount (in moles) of hydrogen gas is contained in 1.85 L of this mixture at 308 K? You work for a marketing firm that has just landed a contract with Run-of-the-Mills to help them promote three of their products: guppy gummies, flopsicles, and mookies. All of these products have been on the market for some time, but, to entice better sales, Run-of-the-Mills wants to try a new advertisement that will market two of the products that consumers will likely consume together. As a former economics student, you know that complements are typically consumed together while substitutes can take the place of other goods. Run-of-the-Mills provides your marketing firm with the following data: When the price of guppy gummies increases by 5%, the quantity of flopsicles sold decreases by 4% and the quantity of mookies sold increases by 5%. Your job is to use the cross-price elasticity between guppy gummies and the other goods to determine which goods your marketing firm should advertise together. The immediate cause of the 2006-2010 economic crisis was: a)the failure of Enron b)greedy financial advisors on Wall Street c)the increase in imports from China the bursting of the U.S. housing bubble d)the bursting of the U.S. housing bubble The perimeter of a rectangle is 230 feet. The short sides are each 30 feet long, but the lengths of the long sides are unknown. Which equation represents this situation?30+2a=2302(30)+2a=2302(30)a=23030a=230 help me please im so far behind and im trying to finish before summer ends im freaking out When the polynomial in P(x) is divided by (x + a), the remainder equals P(a) Choose the equation that represents a line that passes through points (1, 2) and (3, 1). A)4x y = 6 B)x + 4y = 7 C)x 4y = 9 D)4x + y = 2